2009
DOI: 10.1007/s12031-009-9233-4
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Regulation of α7 Nicotinic Receptor Gene (CHRNA7) Expression in Schizophrenic Smokers

Abstract: The α7 neuronal nicotinic receptor gene (CHRNA7) has been implicated in the pathophysiology of schizophrenia by genetic and pharmacological studies. Expression of the α7* receptor, as measured by [ 125 I]α-bungarotoxin autoradiography, is decreased in postmortem brain of schizophrenic subjects compared to non-mentally ill controls. Most schizophrenic patients are heavy smokers, with high levels of serum cotinine. Smoking changes the expression of multiple genes and differentially regulates gene expression in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 87 publications
4
78
0
Order By: Relevance
“…With respect to clinical considerations, a close association between nicotine addiction and schizophrenia has been found (Lohr & Flynn, 1992). Consistent with the hypothesis, that a gene-mediated dysfunction of α7 nAChR (Dome et al, 2010;Freedman et al, 1997;Stephens et al, 2009) underlies impairments seen in schizophrenia , the density of hippocampal [ 125 I]α-BGT binding sites was decreased in schizophrenic patients (Freedman et al, 1995) but was at control levels in schizophrenic smokers (Mexal et al, 2010). Evidence for an involvement of α7 nAChR in Alzheimer's disease (AD) was obtained at about 30 years ago from data showing a significantly reduced number of [ 125 I]α-BGT binding sites in the mid-temporal gyrus from demented patients (Davies & Feisullin, 1981).…”
Section: Alterations Of 7 Nachr In Diseased Brainsupporting
confidence: 64%
“…With respect to clinical considerations, a close association between nicotine addiction and schizophrenia has been found (Lohr & Flynn, 1992). Consistent with the hypothesis, that a gene-mediated dysfunction of α7 nAChR (Dome et al, 2010;Freedman et al, 1997;Stephens et al, 2009) underlies impairments seen in schizophrenia , the density of hippocampal [ 125 I]α-BGT binding sites was decreased in schizophrenic patients (Freedman et al, 1995) but was at control levels in schizophrenic smokers (Mexal et al, 2010). Evidence for an involvement of α7 nAChR in Alzheimer's disease (AD) was obtained at about 30 years ago from data showing a significantly reduced number of [ 125 I]α-BGT binding sites in the mid-temporal gyrus from demented patients (Davies & Feisullin, 1981).…”
Section: Alterations Of 7 Nachr In Diseased Brainsupporting
confidence: 64%
“…PFC deficits are also a component of dementias such as AD, where there is early accumulation of β-amyloid and phosphorylated tau early in the disease, including tangles in layer III pyramidal cells (17). All of these disorders involve genetic alterations (24,(57)(58)(59)(60) or molecular interactions (25,61) of/with α7-nAChR signaling, including evidence of reduced receptor expression in PFC of patients with schizophrenia (22) or autism spectrum disorders (60). Genetic alterations of α7-nAChRs in schizophrenia are particularly well established (18).…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive evidence linking genetic alterations of α7-nAChR to schizophrenia and attentional deficits (18,19), including alterations at the transcription level (20). Recent data have also shown that α7-nAChR expression depends on neuregulin, another molecule linked to schizophrenia (21), and that smoking in schizophrenia may be a form of self-medication, normalizing expression of α7-nAChRs (22). More recent studies have linked α7-nAChRs to autism (23), attention deficit hyperactivity disorder [ADHD (24)], and AD (25), suggesting that a variety of dlPFC disorders are linked to alterations in α7-nAChR signaling.…”
mentioning
confidence: 99%
“…Nicotine's effects on cognition are known to be mediated via α7 nAChRs (Mansvelder et al, 2009). Moreover, smoking has been shown to restore α7 receptor expression in the hippocampus of schizophrenic patients to control levels (Mexal et al, 2010), suggesting a prominent role for α7 nAChR upregulation in the procognitive effect of nicotine.…”
Section: Discussionmentioning
confidence: 99%